Modernizing Tariff Policy - World Bank (World Bank, Washington, DC, 2018)
Tariff modernization will help Bangladesh diversify its export basket. Tariff modernization is at the crux of input competitiveness for efficient manufacturing given that more than 90 percent of the raw material for exportable goods are imported in Bangladesh and the other export incentives like bonded warehouse facilities are not accessible to firms other than Ready Made Garments and a few deemed exporters. Duty drawback system is also designed to discourage traders from claiming it in the first place and cash incentives can only be used as a temporary measure.